การศึกษาลักษณะเนื้อหาในแบบเรียนวิชาภาษาไทยที่เอื้อต่อการพัฒนาทักษะทางภาษาไทยสำหรับนักเรียนระดับประถมศึกษาปีที่ 1 - โพนน้อย, วรินทร (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2019)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาให้ทราบถึงลักษณะเนื้อหาในแบบเรียนวิชาภาษาไทยที่เอื้อต่อการพัฒนาทักษะทางภาษาไทย สำหรับนักเรียนชั้นประถมศึกษาปีที่ 1 การวิจัยครั้งนี้เป็นการวิจัยเชิงคุณภาพ (Qualitative Research) โดยเป็นการศึกษานำร่องเพื่อให้ทราบถึงศึกษาลักษณะเนื้อหาในแบบเรียนวิชาภาษาไทยที่เอื้อต่อการพัฒนาทักษะทางภาษาไทย สำหรับนักเรียนชั้นประถมศึกษาปีที่ 1 โดยศึกษาจากกลุ่มตัวอย่างที่ได้มาโดยวิธีการเลือกแบบเจาะจง (Purposive Sampling) จำนวน 25 คน ประกอบด้วย 1) ผู้เชี่ยวชาญทางภาษาไทย จำนวน 5 คน 2) ครูผู้สอนภาษาไทยระดับประถมศึกษา จำนวน 5 คน 3) ผู้ที่มีประสบการณ์ด้านหลักสูตรและการสอน จำนวน 5 คน 4) ผู้ปกครองของนักเรียนในระดับประถมศึกษา จำนวน 5 คน และ 5) นักเรียนในระดับประถมศึกษา จำนวน 5 คน โดยการสัมภาษณ์เชิงลึกแล้วนำมาวิเคราะห์ผล ผลการวิจัยพบว่าลักษณะเนื้อหาในแบบเรียนวิชาภาษาไทยที่เอื้อต่อการพัฒนาทักษะทางภาษาไทยของนักเรียนระดับประถมศึกษาควรมีลักษณะดังนี้ 1) มีการนำเสนอเนื้อเรื่องที่ใช้ภาพประกอบที่สวยงามในลักษณะของหนังสือภาพ (Picture Book)โดยมีเนื้อหา เน้นคุณลักษะที่พึงประสงค์ที่ต้องการให้เกิดขึ้นกับนักเรียน มีการลำดับเนื้อเรื่องแบบมีเค้าโครงเรื่อง (Story) ประกอบด้วยเนื้อเรื่องทั้งในแบบร้อยแก้วและร้อยกรองมีภาพประกอบเป็นภาพการ์ตูนเสมือนจริงที่มีการลงสีสันสวยงามสอดคล้องกับเนื้อเรื่องในทุกหน้า 2) การเรียงลำดับเนื้อหาแต่ละบทจากง่ายไปหายากทั้งเนื้อหา เรื่องของไวยากรณ์ ทั้งพยัญชนะ สระ และวรรณยุกต์ เพื่อ สร้างการเรียนรู้และความเข้าใจภาษาอย่างเป็นลำดับต่อเนื่อง 3) ลักษณะเนื้อเรื่องมีความสนุกสนาน ตื่นเต้น ส่งเสริมจินตนาการเสมือนให้เด็กได้เข้าไปเป็นส่วนหนึ่งของเนื้อเรื่อง มีตัวละครที่เป็นเด็กในวัยเดียวกับผู้เรียนเป็นตัวหลักในการดำเนินเรื่อง โดยเนื้อเรื่องในแต่ละบทเรียนนั้นควรมีสถานการณ์ที่เชื่อมโยงกัน ความยาวของแต่ละบทไม่ควรเกิน 3 – 5 หน้า 4) มีบทร้องเล่น นิทานพื้นบ้าน หรือวรรณคดีในตอนที่สนุกนานและเหมาะสมกับวัย โดยใช้คำ ข้อความ หรือ รูปประโยคง่ายๆ ไม่ซับซ้อน ใช้ภาษาที่เข้าใจง่าย สุภาพ มีคำซ้ำบ่อย ๆ 5) ในแต่ละบทมีการดำเนินเรื่องที่สนุก รวดเร็ว กระชับ น่าติดตาม และเหตุการณ์ต่าง ๆ จบในบทเรียนนั้น 6) เนื้อหาควรสอดแทรกคติธรรม คุณธรรม จริยธรรม ค่านิยมที่พึงประสงค์ บุคลิกลักษณะนิสัยที่ดี ตลอดจน การเป็นพลเมืองไทยและเป็นพลโลกที่ดี 7) มีประมวลคำศัพท์ท้ายบทเรียนเพื่อการฝึกอ่านการสะกดคำและอธิบายความหมายของคำ และอธิบาย หลักภาษาจากรูปประโยคที่มีอยู่ในเนื้อหาบทเรียน และรูปประโยคอื่น ๆ เพิ่มเติมเพื่อให้ผู้เรียนได้ฝึกซ้ำ ๆ 8) รูปแบบอักษรถูกต้องตามหลักภาษาไทย ในส่วนของเนื้อเรื่องใช้ตัวอักษรสีดำ สีน้ำเงินเข้ม หรือสีเขียวเข้ม แต่ในส่วนของหลักไวยากรณ์นั้นควรใช้สีสันต่าง ๆ เพื่อช่วยเน้นย้ำความเข้าใจ ขนาดของตัวอักษรที่เหมาะสม 24 พอยท์ พิมพ์ลงบนกระดาษปอนด์ที่มีความหนาของกระดาษไม่น้อยกว่า 80 แกรม 9) รูปเล่มของหนังสือควรมีการออกแบบหน้าปกหนังสือให้เป็นรูปตัวละคร ประณีต สวยงาม สีสันสดใสการ เย็บเล่มสวยงาม ประณีต แข็งแรงทนทาน สามารถเปิดอ่านได้ง่ายขนาดของหนังสือไม่ใหญ่และไม่หนาเกินไปในลักษณะของพ็อกเก็ตบุ้ค (Pocket Book) ที่มีขนาดประมาณ 13 x 19 เซนติเมตร สามารถพกพาไปศึกษาในสถานที่ต่าง ๆ ได้สะดวก คำสำคัญ : ลักษณะเนื้อหาในแบบเรียนวิชาภาษาไทย, การพัฒนาทักษะทางภาษาไทย, รูปแบบหนังสือเรียนประถมศึกษาปีที่ 1 ABSTRACT The purpose of this research was to study the content of Thai language learning characteristics that are conducive to the development of Thai language skills for grade 1 students. This research is a qualitative research which is a pilot study to acknowledge the contents of the Thai language characteristics that are conducive to the development of Thai language skills for grade 1 students by studying from the 25 sampling obtained by purposive selection method, consisting of 1) 5 Thai language experts, 2) 5 Thai language teachers for elementary education, 3) 5 people with experience in curriculum and teaching, 4) 5 parents of students in elementary school, and 5) 5 students in elementary school with the in-depth interviews and take results for analysis. The results of the study presented that the content in the Thai language learning characteristics which are conducive to the development of Thai language skills of elementary school students should be as follows: 1) The story should be presented by using beautiful illustrations in the form of picture books with the content that emphasizes the desirable characteristics that occur with students. There is a sequence with a story consisting of both the prose and poetry. There is an illustration of a virtual cartoon that has beautiful colors in accordance with the story on every page. 2) Sorting the content of each chapter from easy to difficult, including grammatical content, consonants, vowels and tone of the language for learning and understanding of languages continuously. 3) The nature of the story is fun, exciting, encouraging imagination as if children were to be part of the story. The story has a character who is a child at the same age as the students as the main character in the story. The story in each chapter has a connected situation with the length of each chapter should not exceed 3 - 5 pages. 4) There are lyrics, folk tales, or literature in an entertaining and age-appropriate manner using words, text or simple and uncomplicated sentences, easy to understand language, as well as polite and repeated words. 5) In each chapter, there is a fun, fast, concise, and interesting story and events in that lesson. 6) Content should include morals, ethics, desirable values, personality, good habits and how to be a good Thai citizen and world citizen. 7) There is a glossary of words at the end of the lesson to practice reading words, spelling, and explaining the meaning of words. It also describes the language of the sentence form that is included in the lesson content and other sentence patterns for students to practice repeatedly. 8) The font format should be correct according to the Thai language. For the content, black, dark blue, or dark green should be used on letters. However, in terms of grammar, the colors should be used to help emphasize the understanding, and the appropriate font size is 24 points. Printed on pound paper with a paper thickness of at least 80 grams 9) For the body of the textbook, the cover of the textbook should be designed to have characters, exquisite, beautiful, and colorful pictures on it. The textbooks should be made beautifully, neatly, durably, easily to read. Moreover, the book must not be too big and not too thick. It should be a pocket book that is about 13 x 19 cm in size, and it must be easy to carry around. Keywords: Characteristics in the Thai Language Learning Textbook, Thai Language Development Skills, Elementary School Textbook Format for Grade 1